2020
DOI: 10.3389/fsurg.2020.601692
|View full text |Cite
|
Sign up to set email alerts
|

Is Vestibular Meniere's Disease Associated With Endolymphatic Hydrops?

Abstract: Background: Vestibular Meniere's disease (American Academy of Ophthalmology and Otolaryngology, 1972) also known as possible Meniere's disease (American Academy of Otolaryngology Head and Neck Surgery, 1995) or vestibular type of atypical Meniere's disease (V-AMD) (Japan Society for Equilibrium Research, 2017) is characterized by an episodic vertigo without hearing loss. Though named as Meniere's disease (MD), this entity may not be caused solely by endolymphatic hydrops (EH).Objective: To estimate the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Attyé et al (44) found that 48.4% of patients with BRV showed vestibular hydrops and/or cochlear hydrops on MRI. Some authors suggest that there is a subtype of vestibular MD presenting with recurrent attacks of vertigo without fluctuating hearing loss and symptoms of aural fullness (45). In the present study, BRV was the most common cause of spontaneous UBN in patients with EVS, two of the four patients with BRV showed mixed SN with a non-predominant upbeat component, and the other two showed pure UBN.…”
Section: Brvsupporting
confidence: 59%
“…Attyé et al (44) found that 48.4% of patients with BRV showed vestibular hydrops and/or cochlear hydrops on MRI. Some authors suggest that there is a subtype of vestibular MD presenting with recurrent attacks of vertigo without fluctuating hearing loss and symptoms of aural fullness (45). In the present study, BRV was the most common cause of spontaneous UBN in patients with EVS, two of the four patients with BRV showed mixed SN with a non-predominant upbeat component, and the other two showed pure UBN.…”
Section: Brvsupporting
confidence: 59%
“…Li et al also detected asymptomatic endolymphatic effusion on the non affected side of 32 patients (18%) through MRI of 178 unilateral Meniere’s patients [ 8 ]. In addition, some scholars also confirmed the existence of cochlear and vestibular hydrops on the opposite side of unilateral Meniere’s disease patients, and the amount of bilateral hydrops in vestibule is higher than that in cochlea [ 9 ]. In our study, 11 of 70 ears of unilateral Meniere’s disease patients had no V-EH, and the most patients had significant hydrops.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, the first problem encountered with the VES/vestibule ratio was that mild vEH was not only reported in the greatest majority of symptomatic ears of MD patients, but also in more than half of the asymptomatic contralateral ears ( 19 , 34 , 58 , 60 ). Moreover, EH has been detected also in healthy individuals ( 11 , 61 , 62 ), and this challenges its correlation with MD ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of ongoing studies is currently aimed at targeting the correlation between the morphologic findings and the symptomatology ("the whole symptoms triad") and, especially, with the results of the functional audio-vestibular testing and with the outcomes of treatment (37,41,48,51,52,62,63,67). In general, the literature agrees that the presence of EH at MRI, independently from the cut-off values for definition of vEH, strongly correlates with the side of the disease in MD patients (47,50), but it lacks specificity in differentiating MD from other inner ear disturbances, in the absence of clinical/instrumental confirmation (64).…”
Section: Recent Advancesmentioning
confidence: 99%